Rancangan Buku Teks Muatan Lokal Sejarah Banjar Untuk Bahan Ajar Sejarah Peminatan SMA Kelas XI di Kalimantan Selatan - Mansyur Mansyur; Rusdi Effendi; Daud Yahya; Mohamad Zaenal Arifin Anis (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The teaching of local history in high schools plays a crucial role in shaping students’ cultural identity and historical awareness of their region. However, the availability of adequate local history textbooks, particularly in South Kalimantan, remains very limited, making it necessary to develop systematic, high-quality textbooks. The research aims to design a Local History textbook for Senior High Schools in South Kalimantan using a descriptive-analytical approach. The design incorporates national book evaluation criteria, book writing models, and textbook writing theories from experts. The results of this textbook design include two main components: the fundamental component, which covers aspects of content, presentation, language, graphics, and safety, and the complementary component, which includes the use of color, glossary, index, and appropriate font sizes. The textbook content is designed for grades X to XII, focusing on the Local History of South Kalimantan. It is structured to help students understand historical concepts through various elements such as concept maps, learning objectives, materials, summaries, and comprehension questions. This textbook is expected to be an effective learning resource for high school students in South Kalimantan.